1995
DOI: 10.1093/brain/118.3.759
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and pathological spectrum of Steele-Richardson-Olszewski syndrome (progressive supranuclear palsy): a reappraisal

Abstract: Seventeen patients with a progressive bradykinetic syndrome and post-mortem findings of neurofibrillary degeneration in cerebral cortex, subcortical nuclei and brainstem were studied. Seven fulfilled currently accepted clinical diagnostic criteria for Steele-Richardson-Olszewski syndrome, whereas the remainder who lacked supranuclear gaze palsy had alternative clinical diagnoses (idiopathic Parkinson's disease, six cases; cerebrovascular disease, two cases; Parkinson's syndrome, one case; Alzheimer's disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
151
3
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(164 citation statements)
references
References 0 publications
6
151
3
4
Order By: Relevance
“…By RNase mapping experiments, we have shown that exon 3 was skipped in 4 to 6% of the total HTH mRNA population in normal adrenal medulla, a proportion similar to that of the previously described HTH-3 and -4 mRNA species (11,12). These novel mRNA species were unusually abundant (5) in adrenal medulla of patients suffering from progressive supranuclear palsy (PSP), which is a severe neurodegenerative disease predominantly characterized by an alteration of the catecholaminergic neurons within the basal ganglia (13). The novel mRNA species encode putative HTH proteins lacking the 74 amino acids of the exon 3.…”
supporting
confidence: 56%
“…By RNase mapping experiments, we have shown that exon 3 was skipped in 4 to 6% of the total HTH mRNA population in normal adrenal medulla, a proportion similar to that of the previously described HTH-3 and -4 mRNA species (11,12). These novel mRNA species were unusually abundant (5) in adrenal medulla of patients suffering from progressive supranuclear palsy (PSP), which is a severe neurodegenerative disease predominantly characterized by an alteration of the catecholaminergic neurons within the basal ganglia (13). The novel mRNA species encode putative HTH proteins lacking the 74 amino acids of the exon 3.…”
supporting
confidence: 56%
“…Conversely, in some atypical parkinsonian syndromes, such as PSP, mainly striatal neurons degenerate (Daniel et al, 1995;Burn and Lees, 2002). Reduced activity of complex I of the mitochondrial respiratory chain has been implicated in both these clinical conditions (Schapira et al, 1990;Dawson and Dawson, 2003;Höglinger et al, 2005Höglinger et al, , 2006Di Filippo et al, 2006;Sherer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, PSP is an atypical parkinsonian syndrome characterized by dorsorostral midbrain atrophy associated with severe neuronal loss in the substantia nigra, loss of striatal GABAergic projecting spiny neurons, and cerebral tau protein pathology (Daniel et al, 1995;Burn and Lees, 2002;Pearce, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have identified alternative clinical phenotypes7, 8 related to PSP pathology in relatively small case series. This led to the description of 2 distinct PSP non‐RS clinical phenotypes by Williams and colleagues, PSP‐parkinsonism (PSP‐P)9 and pure akinesia with gait freezing (PAGF) 10.…”
mentioning
confidence: 88%